2019
DOI: 10.1097/pr9.0000000000000712
|View full text |Cite
|
Sign up to set email alerts
|

Performance of behavioral assays: the Rat Grimace Scale, burrowing activity and a composite behavior score to identify visceral pain in an acute and chronic colitis model

Abstract: Supplemental Digital Content is Available in the Text. The ability of spontaneous behavioral assays to assess chronic pain is limited. In colitis, RGS identified acute and chronic pain, burrowing identified acute pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 35 publications
(54 reference statements)
4
21
0
Order By: Relevance
“…Subsequently, others have reported that chronic pain may be identified using grimace scales in other models, notably colitis (dextran sodium sulphate-induced), cervical radiculopathy (surgical compression model), neuralgia (chronic constriction injury of the infraorbital nerve), orofacial pain (movement or load-induced), spinal cord injury (cord impact model) and migraine (nitroglycerin-induced) in rats and mice. 2,6,48,74,80,112,134,152 These data suggest that limiting application of the MGS and RGS to acute pain may be premature.…”
Section: Physiologic Assessments Of Pain In Laboratory Mice and Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, others have reported that chronic pain may be identified using grimace scales in other models, notably colitis (dextran sodium sulphate-induced), cervical radiculopathy (surgical compression model), neuralgia (chronic constriction injury of the infraorbital nerve), orofacial pain (movement or load-induced), spinal cord injury (cord impact model) and migraine (nitroglycerin-induced) in rats and mice. 2,6,48,74,80,112,134,152 These data suggest that limiting application of the MGS and RGS to acute pain may be premature.…”
Section: Physiologic Assessments Of Pain In Laboratory Mice and Ratsmentioning
confidence: 99%
“…29 In rats, scoring of burrowing behavior has been employed successfully in Hooded Lister, Wistar and Sprague-Dawley strains. 3,29,52,69 Burrowing is reduced in a wide range of pain models in rats and mice, including laparotomy, 4,58-60 colitis and mucositis, 57,74,144 neuropathic pain, 3,52,69,95,124 inflammation, 3,46,95,130,139,144,147 and arthritis. 12,125,126 In addition, many of these studies have confirmed responsiveness, showing either an improvement or return to baseline burrowing behavior following the administration of antiinflammatories and analgesics.…”
Section: Burrowing Behaviorsmentioning
confidence: 99%
“…However, previous studies involved a surgical stimulus [28,29,30], or inflammatory pain model [28], hence pain duration in the current study may have been reduced in comparison to the visceral pain sensation of mucositis. Contrarily, an assumed chronic pain insult caused by tooth movement caused a grimace response in rats for several days post-pain insult [31], as did the presence of colitis [14]. It is noteworthy that in the current study, grimace values were a small fraction of the maximum obtainable score (i.e., 8); often scoring under one.…”
Section: Discussionmentioning
confidence: 72%
“…The disease activity index (DAI) evaluates disease severity based on general clinical observations; overall appearance of the animals, bodyweight loss, rectal bleeding and stool consistency. While an association between clinical signs and pain has been demonstrated in gastrointestinal disorders in human clinical practice, this has not been validated in rodent models of mucositis [3,14]. The open field test is a well validated measure of anxiety in rodent models.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the original derivation of the threshold was in adult PLOS ONE female SD rats that underwent surgery involving the skin and muscular systems. However, recent work showed that the RGS and intervention threshold identified the onset of acute and chronic colitis (a model of visceral pain) in male and female SD rats [20,35]. The RGS and intervention threshold has also been successfully applied to distinguish analgesic effects in female Wistar rats (laparotomy model, analgesic testing) [36,37].…”
Section: Limitations and Future Studiesmentioning
confidence: 99%